2016
DOI: 10.1186/s13195-016-0215-9
|View full text |Cite|
|
Sign up to set email alerts
|

The societal costs of dementia in Sweden 2012 – relevance and methodological challenges in valuing informal care

Abstract: BackgroundIn this study, we sought to estimate the societal cost of illness in dementia in Sweden in 2012 using different costing approaches to highlight methodological issues.MethodsWe conducted a prevalence-based cost-of-illness study with a societal perspective.ResultsThe societal costs of dementia in Sweden in 2012 were SEK 62.9 billion (approximately €7.2 billion, approximately US$9.0 billion) or SEK 398,000 per person with dementia (approximately €45,000, approximately US$57,000). By far the most importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 44 publications
4
67
1
Order By: Relevance
“…It seems that there might be a difference in the care recipients' preferences and the support system in each country. In a nationwide cost estimation study in Sweden, among the societal costs to the social care sector other than institutional care (17.6%), home helper services represented 11.7% of costs and day care services represented 1.7% of costs, which were similar to findings in other European countries . The high prevalence of day services used in the present study might be a characteristic feature of nursing care in Japan.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It seems that there might be a difference in the care recipients' preferences and the support system in each country. In a nationwide cost estimation study in Sweden, among the societal costs to the social care sector other than institutional care (17.6%), home helper services represented 11.7% of costs and day care services represented 1.7% of costs, which were similar to findings in other European countries . The high prevalence of day services used in the present study might be a characteristic feature of nursing care in Japan.…”
Section: Discussionsupporting
confidence: 84%
“…In a nationwide cost estimation study in Sweden, among the societal costs to the social care sector other than institutional care (17.6%), home helper services represented 11.7% of costs and day care services represented 1.7% of costs, which were similar to findings in other European countries. 19 The high prevalence of day services used in the present study might be a characteristic feature of nursing care in Japan. The monetary cost of social care among patients with Table 1 Basic characteristics of participants stratified by long-term care insurance levels 74.3…”
Section: Discussionmentioning
confidence: 68%
“…For example, using the same cohort of patients, annual informal caregiving was valued at US$13,188 using the replacement costs approach but was valued at US$27,789 using the opportunity cost approach [3]. Similarly, a study from Sweden found that informal costs can range from SEK 60 billion to SEK 124 billion depending on the approach used [69]. A systematic review conducted by ADI indicated that the proportion of total disease costs attributed to informal care ranged from 19% to 91% across studies, largely due to differences in the assumptions and approaches used to assess and value informal care [70].…”
Section: Box 2: Indirect Costs-key Takeawaysmentioning
confidence: 99%
“…While non-trivial, this pales in comparison to the total cost of ADRD, which has been estimated at US$259 billion in the US in 2016 alone [77]. Another report using registry data from the Swedish Social Insurance Agency estimated productivity losses in individuals who were prematurely retired or on sick leave due to a dementia diagnosis [69]. At SEK118 million (2012), the productivity losses due to premature retirement or sick leave in Sweden represented only a minor component of total costs.…”
Section: Patients: Productivity Lossesmentioning
confidence: 99%
“…household work or caring for children instead of lost production. For these individuals, the cost of lost production per day was multiplied by 0.35, following the findings of earlier studies (74)(75)(76).…”
Section: Costs Of Sedationmentioning
confidence: 99%